2021
DOI: 10.1111/wrr.12943
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis: Sirtuins at the checkpoints of myofibroblast differentiation and profibrotic activity

Abstract: Fibrotic diseases are still a serious concern for public health, due to their high prevalence, complex etiology and lack of successful treatments. Fibrosis consists of excessive accumulation of extracellular matrix components. As a result, the structure and function of tissues are impaired, thus potentially leading to organ failure and death in several chronic diseases. Myofibroblasts represent the principal cellular mediators of fibrosis, due to their extracellular matrix producing activity, and originate fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 179 publications
(308 reference statements)
0
7
0
Order By: Relevance
“…On the contrary, scientific discoveries have confirmed that early stage of fibrotic diseases is reversible, the effective measures contain removal or elimination of the causative agent. But it seems impossible to timely occurrence reversible and appropriately wound-healing, used to avoid complications ( 6 , 7 ). Despite decades of research on fibrotic diseases, few effective and clinical anti-fibrotic drugs have been discovered yet ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, scientific discoveries have confirmed that early stage of fibrotic diseases is reversible, the effective measures contain removal or elimination of the causative agent. But it seems impossible to timely occurrence reversible and appropriately wound-healing, used to avoid complications ( 6 , 7 ). Despite decades of research on fibrotic diseases, few effective and clinical anti-fibrotic drugs have been discovered yet ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…We will further elaborate on the consequences of lost mechanical integrity in conditions of skin injury, with a spotlight on fibroblasts and myofibroblasts. Other aspects of fibroblast-to-myofibroblast regulation 9 and other fibroblast activities, such as inflammatory actions are discussed elsewhere. 10 After a brief survey of major fibrillar ECM protein components in the healthy skin, we will address the origins and heterogeneity of skin fibroblasts and how they respond to various ECM cues.…”
Section: Introductionmentioning
confidence: 99%
“…6). This was surprising, as it would be expected that a change in tissue structure would take more time [51]. Although this case is not representative, it provides interesting food for thought regarding the mechanisms behind this improvement in morphology.…”
Section: Discussionmentioning
confidence: 88%